First-Order Optimality Conditions in Multiobjective Optimization Problems: Differentiable Case - Rizvi, MM; Hanif, Muhammad; Waliullah, GM (GANIT: Journal of Bangladesh Mathematical Society, 2011)
T. Maeda gave some constraint qualifications to get positive Lagrange multipliers associated with the vector-valued objective function and under these conditions, he derived Karush-Kuhn-Tucker (KKT) type necessary conditions for inequality constraints. In this paper, we have defined these Maeda-type constraint qualifications under different sets and have derived KKT type necessary conditions for both equality and inequality constraints. GANIT J. Bangladesh Math. Soc. (ISSN 1606-3694) 29 (2009) 99-105 DOI: http://dx.doi.org/10.3329/ganit.v29i0.8519